Avaliação imuno-histoquímica da proliferação e morte celular em neoplasias mamárias malignas caninas - Martins, Daniela de Carvalho (2008)
Canine mammary neoplasia is the most common found in the bitch. Researches are being carried out at present as they can be used as an important model for mammary carcinogenesis in women. Classification is the essential characteristic for prognosis and diagnostic evaluation, so that an adequate clinicalsurgical conduct may be carried out, but, as this approach sometimes presents difficulties, other techniques are then used. The use of cell proliferation markers is an objective and quantifiable method, more sensitive and specific to assess the mitotic activity in neoplasia, rather than the mitosis count, as it is done in conventional histology, to identify apoptosis. Therefore, a balance between proliferation and cell death during tumor growth is an important factor, where the process of programmed cell-death is involved. The purpose of this work is to assess the proliferative and apoptic activity in canine malignant mammary neoplasia, associating the results. Sixty-one cases of bitches with malignant mammary neoplasia were used in this work. Neoplasias were classified according to the World Health Organization classification; the immunohistochemical technique was applied by means of the LSAB method; anti-PCNA, anti-Ki-67 were used as primary antibodies, as well as cleaved anti-Caspase-3. Considering 61 samples, by means of the histopathology procedure, five carcinosarcomas, nine carcinomas in mixed tumors, six complex tubular adenocarcinomas, 12 primary tubular adenocarcinomas, 13 complex papilliferous adenocarcinomas, 15 primary papilliferous adenocarcinomas and a primary solid carcinoma were observed. No breed predisposition was found and most of the animals with the disease were between 5 and 10 years old. In the malignant mammary neoplasia, the expression of PCNA and Ki-67 showed to be greater in number than the expression of cleaved Caspase-3 and a positive correlation among the expressions of PCNA and Ki-67 was observed. Regarding primary tubular adenocarcinomas, Ki-67 presented a significant negative correlation with the cleaved Caspase-3 and PCNA showed a negative correlation tendency, which was also significant with the cleaved Caspase-3. The proliferation and cell death study arises to add more information on neoplasic behavior. The association of these prognostic markers to other factors commonly used in routine procedures can complement the already existing classification of neoplasia, providing expressive support in the elaboration of a more precise diagnostic and prognosis of mammary neoplasia, thus contributing to the patient s extra life, facilitating a more adequate and individualized clinical treatment. This may also be used as an experimental model in the studies that compare the human mammary neoplasia